1994
DOI: 10.1002/ajh.2830470209
|View full text |Cite
|
Sign up to set email alerts
|

Results of secondary prophylaxis in children with severe hemophilia

Abstract: In this study, 13 children with severe hemophilia were given routine replacement infusions of factor VIII or IX to treat arthropathy. The children who had a mean age of 6.9 years (range 2.0-12.5) at initiation of prophylaxis had experienced an average of 43 acute hemorrhages (range 8-127) in the year prior to prophylaxis, of which a mean of 24 (range 5-46) were into joints. Therapy was begun in five children, using factor VIII concentrate at 20 U/kg three times a week, and one boy received factor IX concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
148
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 5 publications
14
148
3
Order By: Relevance
“…When to start prophylaxis is an important issue, because it has been shown that early prophylaxis can prevent joint damage 7 and late prophylaxis may decrease but does not stop further deterioration of damaged joints over a period of several years. 3,21 In the present study, prophylaxis only seemed to prevent arthropathy in most patients when started before the third joint bleed. The first question remains: Should we start prophylaxis before the first joint bleed?…”
Section: Discussionmentioning
confidence: 97%
“…When to start prophylaxis is an important issue, because it has been shown that early prophylaxis can prevent joint damage 7 and late prophylaxis may decrease but does not stop further deterioration of damaged joints over a period of several years. 3,21 In the present study, prophylaxis only seemed to prevent arthropathy in most patients when started before the third joint bleed. The first question remains: Should we start prophylaxis before the first joint bleed?…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that prophylaxis started later in life does not halt the progression of arthropathy. 18 The association between employment and HRQol should be interpreted with caution. Many factors may influence HRQol, such as viral infections and the presence of arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Current standard treatment for hemophilias is based on replacement of the deficient factor with frequent intravenous injections of recombinant protein. This therapy has been shown to be effective in limiting acute bleeds and reducing mortality and morbidity (Manco-Johnson et al, 1994;Lofqvist et al, 1997). However, current replacement is unsatisfactory and presents several problems including complications in frequent venous access, product supply, inhibitor formation, allergic reactions, and thrombosis (Ragni, 2004).…”
mentioning
confidence: 99%